THE EFFECT OF SERVICE QUALITY AND HOSPITAL IMAGES ON PATIENT SATISFACTION (SURVEY OF OUTPATIENTS AT SARASWATI CIKAMPEK GENERAL HOSPITAL) - Diputri, Diana Rizqiah; Yusuf, Abdul (Manajemen Bisnis, 2019)
This study aims to examine and analyze the effect of service quality and hospital image on outpatient satisfaction at the Saraswati Cikampek General Hospital. This research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses, and making conclusions and suggestions. The sample in this study amounted to 400 respondents. The results of this study are that there is a strong and direct correlation between Service Quality and Hospital Image. There is a partial effect of Service Quality on Patient Satisfaction of 21.7%. And the partial effect of the Hospital Image on Patient Satisfaction is 49.5%, and the simultaneous effect of Food Quality and Price on Purchasing Decisions is 71.2%, while the remaining 28.8% is the influence of other variables not examined.Keywords: Service Quality, Hospital Image, Patient Satisfaction